2024
DOI: 10.1146/annurev-publhealth-040617-013544
|View full text |Cite
|
Sign up to set email alerts
|

Data Resources for Conducting Health Services and Policy Research

Abstract: Rich federal data resources provide essential data inputs for monitoring the health and health care of the US population and are essential for conducting health services policy research. The six household surveys we document in this article cover a broad array of health topics, including health insurance coverage (American Community Survey, Current Population Survey), health conditions and behaviors (National Health Interview Survey, Behavioral Risk Factor Surveillance System), health care utilization and spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…This study used de-identified administrative claims data from the OptumLabs® Data Warehouse (OLDW), which includes medical and pharmacy claims, laboratory results, and enrollment records for commercial and Medicare Advantage (MA) enrollees. The database contains longitudinal health information on over 200 million enrollees and patients, representing a diverse mix of ages, ethnicities, and geographical regions across the USA [19, 20]. New users of anticoagulant medication (either DOACs or warfarin) between October 1, 2010 and September 30, 2017 were identified via pharmacy claims with the first prescription date defined as the index anticoagulant date.…”
Section: Methodsmentioning
confidence: 99%
“…This study used de-identified administrative claims data from the OptumLabs® Data Warehouse (OLDW), which includes medical and pharmacy claims, laboratory results, and enrollment records for commercial and Medicare Advantage (MA) enrollees. The database contains longitudinal health information on over 200 million enrollees and patients, representing a diverse mix of ages, ethnicities, and geographical regions across the USA [19, 20]. New users of anticoagulant medication (either DOACs or warfarin) between October 1, 2010 and September 30, 2017 were identified via pharmacy claims with the first prescription date defined as the index anticoagulant date.…”
Section: Methodsmentioning
confidence: 99%
“…Many population-based datasets have placed restrictions or moratoriums on accessing geographic-specific identifiers, including urban–rural status; however, in recent years, widely used datasets such as the National Health Interview Survey and BRFSS have begun incorporating such variables into their public-use files with minimal missingness. Unfortunately, many datasets are only available to access at federal Research Data Centers (RDCs), with costly data application/analysis fees, and some data remain masked because of privacy concerns (e.g., Medical Expenditures Panel Survey, Medicare data) [ 202 , 203 ]. Finally, because of administrative constraints and sampling approaches used in many population-based surveys, it is difficult to reach the sample sizes necessary to look at combinations of social strata (i.e., racial/ethnicity by rurality).…”
Section: Implications/recommendationsmentioning
confidence: 99%
“…2). This is likely due to the absence of data from Kaiser Permanente, the largest healthcare insurer in California [17, 18]. The distribution of base sample population located within an MSA (urban or suburban region) or outside of an MSA (rural region) were 65.7% (66 million) and 10.2% (10 million) for MarketScan or 95.8% (259 million) and 3.9% (10 million) for IDV.…”
Section: Resultsmentioning
confidence: 99%